Neighborhood bystander intervention in intimate partner abuse: The role of social cohesion. Issue 3 (26th November 2018) - Lucero, Jessica L.; Roark, Jennifer; Patton, Andrea
Abstract: This study examines the relationships among individual beliefs about intimate partner abuse (IPA), attitudes about IPA reporting, social cohesion, and the intention of intervening in neighborhood IPA. Data for this study come from a larger cross‐sectional, community‐based study in which participants ( N = 1, 626) were surveyed face to face using stratified random sampling in targeted communities in a Mountain West state (i.e., drop‐off, pick‐up method) and online using social media outreach in targeted communities. Linear regression results indicated that participants were less likely to intervene in IPA situations in their neighborhood if they held beliefs about the private nature of IPA or feared retaliation. Additionally, social cohesion was positively associated with participants' intention of intervening in IPA situations in their neighborhood. Our findings suggest potential avenues for community intervention that attempt to build communitywide beliefs that IPA is a community‐level concern and one that demands attention from the entire community.